A Study on the condensation of o-Phthalaldehydic Acid With Primary Hetero Aromatic amines-Part VIII*: Synthesis of N-(3-Phthalidyl)amines - Al-Hamdany, R.; Fataftah, Z.; Betro, A.R. (Asian Journal of Chemistry, 2010)
In this paper the condensations of o-phthalaldehydic acid with twelveprimary heterocyclic amines are reported. The reaction occurred selectivelyat carbon-3 of the lactol form of the acid, affording in all the cases studiedN-(3-phthalidyl)-amines (4) exclusively. None of the Schiff bases of type(5) have been formed. The structures of the isolated products were confirmedfrom their spectral and analytical data.